HUMAN-RELATED FACTORS OF ANTIMICROBIAL RESISTANCE - Belamarić, Gordana (Medicinski podmladak, 2024)
The global issue of antimicrobial resistance stems from the irrational use of antibiotics in humans, animals, and agriculture, inadequate sanitation, international travel and trade, and challenges within healthcare organizations including financing of healthcare. Recent literature indicates that antimicrobial resistance spreads between countries faster than previously assumed and the COVID-19 pandemic has just exacerbated this issue. Addressing this problem requires globally coordinated and multisectoral interventions. The interaction between humans, animals, and the environment is complex, providing numerous pathways for the transmission and spread of antimicrobial resistance. The causes of the resistance that are related to human population could be classified into several categories, such as inappropriate use of antimicrobials in medicine, inadequate sanitation and hygiene, but also the issues of widespread use of cosmetics with antibiotics, detergents, and biocides. Factors contributing to irrational antibiotic use in humans include excessive prescribing in primary healthcare, irrational use in hospitals, and low awareness and knowledge levels regarding rational antibiotic use at the population level. Addressing this necessitates the consideration of a many factors, including the organization of healthcare systems, population demographics, patterns of antibiotics prescription and usage, among others. This review underscores the complexity of antimicrobial resistance, stressing the need for comprehensive measures across different levels to control and suppress its development and spread. Since antimicrobial resistance puts many of the gains of modern medicine at risk, making infections more complicated to treat and other medical procedures and treatments riskier, urgent attention and action of all public health stakeholders globally is essential.
Keywords: Antimicrobial resistance; antibiotic misuse and overuse; over-prescription of antibiotics